Introduction to Programming Languages: Programming in C, C++, Scheme, Prolog, C#, and SOA - Yinong Chen
Chapter 1: Basic Principles of Programming Languages. - Introduction. - Structures of programming languages. - Data types and type checking. - Program processing and preprocessing. - Program development. - Chapter 2: The Imperative Programming Languages, C/C++. - Getting started with C/C++. - Control structures in C/C++. - Data and basic data types in C/C++. - Complex types. - Compound data types. - Standard input and output, files, and file operations. - Functions and parameter passing. - Recursive structures and applications. - Modular design. - Case Study: Putting All Together. - Chapter 3: The Object-Oriented Programming Language, C++. - A long program example: a queue and a priority queue written in C++. - Class definition and composition. - Memory management and garbage collection. - Inheritance. - File operations in C++. - Exception handling. - Parallel computing and multithreading. -Chapter 4: The Functional Programming Language, Scheme. - From imperative programming to functional programming. - Prefix notation. - Basic Scheme terminology. - Basic Scheme data types and functions. - Lambda-calculus. - Define your Scheme procedures and macros. - Recursive procedures. - Define recursive procedures on data types. - Higher-order functions. - Chapter 5: The Logic Programming Language, Prolog. - Basic concepts of logic programming in Prolog. - The prolog execution model. - Arithmetic operations and database queries. - Prolog functions and recursive rules. - List and list manipulation. - Flow control structures. - Prolog application in Semantic Web. - Chapter 6: Fundamentals of the Service-Oriented Computing Paradigm. - Introduction to C#. - Service-oriented computing paradigm. - Service providers: programming web services in C#. - Publishing and searching web services using UDDI. - Building applications using ASP.NET. - Silverlight and pHone applications development. - Cloud computing and big data processing.